2019
DOI: 10.1021/jacs.9b10346
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Tricyclic Bridges Including Neighboring Rings for Understanding Raman Spectra of Zeolites

Abstract: Raman spectroscopy of network solids such as zeolites is critical for shedding light on collective vibrations of medium-range structures such as rings that exist in crystals and that form during crystallization processes. Despite this importance, assignments of Raman spectra are not completely understood, though it is often assumed that Raman bands can be assigned to individual rings. We report a systematic zeolite synthesis, spectroscopy, and periodic DFT study of several all-silica zeolites to test this assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…Raman spectroscopy is a powerful method to probe the structure information of zeolites and study the crystallization mechanisms. 47 In particular, UV Raman spectroscopy can avoid the issue of fluorescence caused due to hydration or the presence of OSDAs and consequently enhance the sensitivity in studying zeolite precursors. 48–50 To confirm the applicability and sensitivity of UV Raman spectroscopy in characterizing the dealuminated FAU zeolites, we first compared the UV Raman spectra of the dealuminated FAU zeolites and the parent from the 320HOA series (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy is a powerful method to probe the structure information of zeolites and study the crystallization mechanisms. 47 In particular, UV Raman spectroscopy can avoid the issue of fluorescence caused due to hydration or the presence of OSDAs and consequently enhance the sensitivity in studying zeolite precursors. 48–50 To confirm the applicability and sensitivity of UV Raman spectroscopy in characterizing the dealuminated FAU zeolites, we first compared the UV Raman spectra of the dealuminated FAU zeolites and the parent from the 320HOA series (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies had revealed that aluminosilicate rings with a larger ring size or T−O−T bond angle would have a lower vibrational frequency (i.e., showing a Raman shift at lower wavenumber). 34,38 The solid product at 0 h (Figure 1D, 0 h) shows a broad band at ca. 200−500 cm −1 , and the maximum Raman intensity appears at the 4R-region (ca.…”
Section: Resultsmentioning
confidence: 99%
“…We also tracked the changes in the solid phase by Raman spectroscopy (Figure D), which is an effective method for identifying the rings (and their neighbor structures) in the zeolite framework . For zeolite X, the bands at 291 and 374 cm –1 are the typical signals of D6R; the peak at 514 cm –1 represents the vibration of 4-membered ring (4R); and the bands at ca.…”
Section: Resultsmentioning
confidence: 99%
“…1d, microstructures such as 4-and 6-rings (4 and 6Rs) originating from the parent FAU changed signicantly. In particular, the peaks at approximately 300 cm À1 , attributed to the 6R [29][30][31] decreased markedly and had signicantly broadened. Additionally, the peaks at approximately 550 cm À1 , attributed to 4R 29-31 also decreased and broadened, but not as much as those of the 6R.…”
Section: Resultsmentioning
confidence: 98%